2003
DOI: 10.1002/jctb.867
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic and photochemical degradation of aniline using concentrated solar radiation

Abstract: The photocatalytic and photochemical degradations (PCD) of aniline using concentrated solar radiation were studied. The photochemical reaction takes place on the surface of the catalyst material. Therefore, the adsorption behavior of aniline on the catalyst was also studied. The rates of aniline degradation in the case of the photocatalytic process were compared with the photochemical method. The effects of the presence of anions and cations, which are commonly present in industrial wastewaters, are reported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 22 publications
(40 reference statements)
4
50
0
Order By: Relevance
“…Chlorobenzene is a strongly adsorbing and rapidly degrading species as compared with phenol, 11 nitrobenzene, 12 benzoic acid, 13 para-hydroxy benzoic acid 14 and aniline. 15 Therefore, extremely low loadings of catalyst were required in the case of chlorobenzene.…”
Section: Effect Of Catalyst Loadingmentioning
confidence: 99%
“…Chlorobenzene is a strongly adsorbing and rapidly degrading species as compared with phenol, 11 nitrobenzene, 12 benzoic acid, 13 para-hydroxy benzoic acid 14 and aniline. 15 Therefore, extremely low loadings of catalyst were required in the case of chlorobenzene.…”
Section: Effect Of Catalyst Loadingmentioning
confidence: 99%
“…These results indicate that the ortho and para substitution of the target molecule dominate in the chlorination process, which should be due to the high reactivity of the ortho and para positions of aniline. [2] There are two possible mechanisms for the formation of CAs: (1) addition of Cl and Cl 2 À to the aromatic ring directly (see Reactions 1, 2) and (2) reaction of Cl and Cl 2 À with the anilino radical or its cation. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The largest use of aniline is to make isocyanates, especially methyl diphenyl diisocyanate. [2] Most research has focussed on the complete mineralisation of aniline, in which the total organic carbon (TOC)-chemical oxygen demand (COD) deletion percentage was often the important assessment index discussed. [3][4][5] Piccinini et al [6] found that the aniline remained unaltered when irradiated without catalyst (TiO 2 ), and the oxidative pathway of forming aminophenols dominated in the presence of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Several physical, chemical and biological methods are available for the removal of dyes from wastewater such as; flocculation and coagulation (Ogutveren, Gonen, & Koparal, 1992;Riera Torres, Guti errez-Bouz an, & Crespi, 2010), biosorption (Sarma, Sarma, & Bhattacharyya, 2008), precipitation (Tan, Teng, & Mohd Omar, 2000), membrane filtration (Koyuncu, Topacik, & Yuksel, 2004), electrochemical techniques (Edip & Erol, 2010), microbial decolorization (Hatchinson & Robinson, 1990) and photodegradation (Xu & Langford, 2001). Numerous materials are also used for the degradation or removal of dyes such as; zeolite (Dogan, Akgul, et al, 2007), perlite (Vijayakumar, Tamilarasan, & Dharmendirakumar, 2012), sepiolite (Ozcan, Oncu, & Ozcan, 2006), fly ash (Khare, Panday, Srivastava, & Singh, 1987), plant materials (Vaughan, Seo, & Marshall, 2001), coir pith (Namasivayam et al, 2001), metal alloys (Tang & Chen, 1996), hydrogen peroxide (Kamble, Sawant, Schouten, & Pangarkar, 2003;Mehrdad & Hashemzadeh, 2010) and metal electrodes (Mohan, Balasubramanian, & Basha, 2007).…”
Section: Introductionmentioning
confidence: 97%